Auxetic Cardiac Patches with Tunable Mechanical and Conductive Properties toward Treating Myocardial Infarction. (10th April 2018) - Kapnisi, Michaella; Mansfield, Catherine; Marijon, Camille; Guex, Anne Geraldine; Perbellini, Filippo; Bardi, Ifigeneia; Humphrey, Eleanor J.; Puetzer, Jennifer L.; Mawad, Damia; Koutsogeorgis, Demosthenes C.; Stuckey, Daniel J.; Terracciano, Cesare M.; et al.
Abstract: An auxetic conductive cardiac patch (AuxCP) for the treatment of myocardial infarction (MI) is introduced. The auxetic design gives the patch a negative Poisson's ratio, providing it with the ability to conform to the demanding mechanics of the heart. The conductivity allows the patch to interface with electroresponsive tissues such as the heart. Excimer laser microablation is used to micropattern a re‐entrant honeycomb (bow‐tie) design into a chitosan‐polyaniline composite. It is shown that the bow‐tie design can produce patches with a wide range in mechanical strength and anisotropy, which can be tuned to match native heart tissue. Further, the auxetic patches are conductive and cytocompatible with murine neonatal cardiomyocytes in vitro. Ex vivo studies demonstrate that the auxetic patches have no detrimental effect on the electrophysiology of both healthy and MI rat hearts and conform better to native heart movements than unpatterned patches of the same material. Finally, the AuxCP applied in a rat MI model results in no detrimental effect on cardiac function and negligible fibrotic response after two weeks in vivo. This approach represents a versatile and robust platform for cardiac biomaterial design and could therefore lead to a promising treatment for MI. Abstract : Micropatterning cardiac patches with a re‐entrant honeycomb design by excimer laser microablation allows for tunability of the mechanical properties of a cardiac patch. The auxetic nature of this pattern improves the conformability of a material to native heart tissue, while maintaining the bulk properties of the material such as conductivity, allowing mechanical and conductive integration with native cardiac tissue.